Faktor-Faktor Yang Berhubungan Dengan Musculoskeletal Disorders Pada Pekerja Pembuat Batu Bata Di Desa Kajhu Kecamatan Baitussalam Aceh Besar Tahun 2022 - Savira Fitri; Wardiati Wardiati; Tahara Dilla Santi (CV. Pusdikra Mitra Jaya, 2023)
Occupational health and safety is an important part of the protection of the health of workers, especially to overcome the problem of work-related diseases. MSDs disorders are a group of disorders that affect the bones, joints, muscles and the body's connective tissues. This study aims to determine the factors associated with Musculoskeletal Disorders Health in Brick Making Workers in Kajhu Village, Baitussalam District, Aceh Besar in 2022. This research is an analytical descriptive with a cross sectional design. Data collection was carried out by interviewing using a questionnaire. The population in this study were brick making workers in Kajhu Village, Baitussalam District, Aceh Besar in 2022 with a total of 40 respondents. The sample is determined by using total sampling technique. The statistical test used is Chi Square. The results showed that there was no relationship between tenure (p = 0.431), and there was a relationship between length of work (p = 0.42), history of MSDs (p = 0.010) and gender (p = 0.048) with musculoskeletal disorders. The conclusion of this study is that the length of service is not related to MSDs complaints in brick makers. Meanwhile, length of work, history of MSDs and gender are related to complaints of health. also increase awareness of the prevention and treatment of musculoskeletal disorders.